Oral Fludrocortisone Test for Salt-Sensitive Screening in Hypertensive Patients: A Randomized Crossover Trial. (15th November 2018) - Pio-Abreu, Andrea; de Castro, Isac; da Silva, Giovanio Vieira; Ortega, Katia Coelho; Mion, Decio
Abstract : Background . Salt sensitivity is associated with an increased cardiovascular risk, but the gold standard method (diet cycles) requires 24-h urine samples and has poor patient compliance. Objectives . Test the hypothesis that oral fludrocortisone (0.4 mg per day for 7 days) is a good alternative in identifying salt-sensitive patients. Methodology . We conducted a randomized crossover study with 30 hypertensive individuals comprising the following steps: (1) washout; (2) phase A (low- and high-sodium diet cycles); (3) washout 2; (4) phase B (fludrocortisone test). Phase A and B steps were performed in a random way. Consistent with the literature, we found that 53.3% were salt-sensitive according to the reference test. Using the ROC curve, the fludrocortisone test defined salt sensitivity by a median blood pressure increase of ≥3 mmHg. A good accuracy of fludrocortisone in detecting salt sensitivity was observed (AUC: 0.732±0.065; p<0.001), with 80% sensitivity and 53% specificity. Conclusion . The fludrocortisone test is a good option for screening salt sensitivity in hypertensive patients. However, the low specificity prevents this test from being an ideal substitute to the labor-intensive diet cycles exam in the definition of salt sensitivity. This clinical trial is registered with NCT01453959 .